Febrile neutropenia in a patient with non-small-cell lung cancer treated with atezolizumab: A case report. (2021) - Seguchi, Kyosuke; Nakashima, Kei; Terao, Toshiki; Takeshita, Gaku; Nagai, Tatsuya; Tanaka, Yu
Abstract: Hematological immune-related adverse events (hem-irAEs) related to immunotherapy have not been extensively characterized, and there is no report of neutropenia caused by atezolizumab administration. Herein, we report a case of febrile neutropenia caused by a hem-irAEs due to atezolizumab, which was treated with granulocyte-colony stimulating factor (G-CSF) and antibiotic prophylaxis. It is important that oncologists be aware of the hematological toxicities of immune checkpoint inhibitors (ICIs). Furthermore, antibiotics and G-CSF should be administered until absolute neutrophil count recovery in cases of febrile neutropenia complicated by atezolizumab. Systemic corticosteroids should not be administered because they can accentuate the risk of infection.